Arabic Affixed Word Mastery Among Pre-University Students In Islamic Religious Schools - Yahya, Siti Khadizah; Baharudin, Harun (Ijaz Arabi Journal of Arabic Learning, 2024)
Affixed vocabulary is very important in learning Arabic vocabulary. Studies on Arabic affixed vocabulary in Malaysia show a lack of research on the weak aspects of affixed vocabulary among students at the pre-university level. Therefore, this study was conducted to identify the level of mastery of affixed vocabulary and the problematic vocabulary types for students to master. This quantitative study uses a survey method by distributing affixed vocabulary tests to collect data based on the research objectives. The sample consisted of 144 STPM students following the pre-university program at the Selangor State Islamic Religious Schools. Stratified random sampling was used for sample selection. The findings show that the mastery level of Arabic-affixed vocabulary among STPM students at Selangor State Islamic Religious Schools could be better. The final result revealed that the aspect of complex affixed vocabulary to mastery is sahih mahmuz al-ayn, mu’tal ajwaf, mu’tal naqis, mu’tal lafif mafruq dan mu’tal lafif maqrun. This result shows that the functions of the derivational system are essential skills for mastering the types of affixed words in Arabic. Hence, teachers, lecturers, and practitioners involved in Arabic language learning are suggested to use the skill to enhance students' vocabulary mastery.